Social scientific research on the American West: current debates, novel methods, and new directions - Paul Berne Burow; Kathryn McConnell; Justin Farrell (Environmental Research Letters, 2019)
Reviewing recent social science research on the western United States from multiple disciplines, we present a state-of-the-art synthesis for scholars and policymakers focused on the socioecological future of this distinctive region. We address four core topics: (1) Migration and population change , focusing on the movements of people across the US West, and the ways that these population shifts are both shaped by and shaping the rise of ‘New West’ economies. (2) Environmental governance , synthesizing work on non-federal government institutions’ interactions with the environment, including local/regional government agencies, Indigenous nations, and non-governmental organizations—all of which shape environmental quality and resource access for communities. (3) Place, culture, and belonging , which concerns how people find meaning in their environment and locate their sense of place in the region given changing social and natural landscapes. (4) Research methodologies , with a specific focus on blending cutting-edge machine learning, and social network approaches with well-established ethnographic, demographic, and survey-based methods. We then map out a future interdisciplinary agenda for the policy-relevant study of social and environmental change in the US West. Our approach stresses the importance of mixed method social research and a robust understanding of how culture, values, and identities intersect with ecological changes on landscapes to shape the well-being of people and ecosystems.